BIOLOGICAL EFFECTIVENESS OF THE ACARACIDE PROMAYT 73 % EC AGAINST SPIDER MITES IN APPLE ORCHARDS IN KHORAZM REGION - D. A. Obidjanov; B. Matniyozov (Web of Journals Publishing, 2024)
In the conditions of Khorezm region, Promayt against spider mite, 73% ec., had a high biological effect when applied at the rate of 0.6-0.8 l/ha and did not show any negative effect on the crop. It is recommended to use the promite in consumption rate of 0.6-0.8 l/ha against spider mite in apple orchards in conditions of Khorezm region.
Keywords: Apple, spider mite, pesticide, biological effect, yield, pest control, acaracide.